AlPcS4-PDT for gastric cancer therapy using gold nanorod, cationic liposome, and Pluronic® F127 nanomicellar drug carriers - Xin J (Dove Medical Press, 2018)
Jing Xin,1,* Sijia Wang,1,* Bing Wang,1 Jiazhuang Wang,1 Jing Wang,1 Luwei Zhang,1 Bo Xin,2 Lijian Shen,1 Zhenxi Zhang,1 Cuiping Yao1 1Key Laboratory of Biomedical Information Engineering of Education Ministry, Institute of Biomedical Analytical Technology and Instrumentation, School of Life Science and Technology, Xi’an Jiaotong University, Xi’an, Shaanxi, China; 2School of Innovation and Entrepreneurship, Xi’an Fan Yi University, Xi’an, Shaanxi, China *These authors contributed equally to this work Purpose: As a promising photodynamic therapy (PDT) agent, Al(III) phthalocyanine chloride tetrasulfonic acid (AlPcS4) provides deep penetration into tissue, high quantum yields, good photostability, and low photobleaching. However, its low delivery efficiency and high binding affinity to serum albumin cause its low penetration into cancer cells, further limiting its PDT effect on gastric cancer. In order to improve AlPcS4/PDT effect, the AlPcS4 delivery systems with different drug carriers were synthesized and investigated. Materials and methods: Gold nanorods, cationic liposomes, and Pluronic® F127 nanomicellars were used to formulate the AlPcS4 delivery systems. The anticancer effect was evaluated by CCK-8 assay and colony formation assay. The delivery efficiency of AlPcS4 and the binding affinity to serum proteins were determined by fluorescence intensity assay. The apoptosis and necrosis ability, reactive oxygen species and singlet oxygen generation, mitochondrial transmembrane potential and ([Ca2+]i) concentration were further measured to evaluate the mechanism of cell death. Results: The series of synthesized AlPcS4 delivery systems with different drug carriers improve the limited PDT effect in varying degrees. In contrast, AlPcS4 complex with gold nanorods has significant anticancer effects because gold nanorods are not only suitable for AlPcS4 delivery, but also exhibit enhanced singlet oxygen generation effect and photothermal effect to induce cell death directly. Moreover, AlPcS4 complex with cationic liposomes shows the potent inhibition effect because of its optimal AlPcS4 delivery efficiency and ability to block serum albumin. In addition, AlPcS4 complex with Pluronic F127 exhibits inferior PDT effect but presents lower cytotoxicity, slower dissociation rate, and longer retention time of incorporated drugs; thus, F127–AlPcS4 is used for prolonged gastric cancer therapy. Conclusion: The described AlPcS4 drug delivery systems provide promising agents for gastric cancer therapy. Keywords: drug delivery carriers, AlPcS4, gastric cancer therapy, gold nanoparticles, cationic liposome, nanomicelle